Training Workshop report Implementation of the CSA Monitoring to assess adoption of Climate Smart Agricultural options and related outcomes in Kaffrine Climate-Smart village (Senegal) - Bonilla Findji, Osana; Andrieu, Nadine (2019)
Led by the International Center for Tropical Agriculture (CIAT), the Climate Change, Agriculture and Food Security (CCAFS) Program is a collaboration among all 15 CGIAR Research Centers. It brings together some of the world's best researchers in agricultural science, climate science, environmental and social sciences to identify and address the most important interactions, synergies and trade-offs between climate change and agriculture. CCAFS aims to define and implement a uniquely innovative and transformative research program to help vulnerable rural communities adjust to global changes in climate and overcome the threats posed to agriculture and food security. Fully aligned with this global effort, CIAT together with ICRAF, ICRISAT and ILRI started implementing the EU-IFAD funded project “Building livelihoods and resilience to climate change in East & West Africa”. The projects’ overall goal will be achieved through supporting large-scale adoption of climate-smart agricultural (CSA) technologies and practices and fulfilling two main objectives